HUBUNGAN GAYA BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 43 MERANGIN - Nanda Aprilia (Mat-Edukasia, 2021)
This research study aims to describe and determine the relationship between student learning styles and mathematics learning outcomes of class VIII students of SMP Negeri 43 Merangin in the academic year 2020/2021. This study used a descriptive-correlational design. The population and research sample were students of class VIII SMP N 43 Merangin in the academic year 2020/2021 which consisted of 4 classes with a total of 116 students. Sampling using the Taro Yamane formula obtained a sample of 53 students with a simple random sampling technique (random) with a lottery model to determine the sample for each class. The data analysis technique was calculated using Person Product Moment correlation, normality test and linearity test, while hypothesis testing used the correlation formula and the Z test. 2020/2021 lesson.